Multichannel Delivery in Healthcare: The Impact of Telemedicine Centers in Southern India - Delana, Kraig; Deo, Sarang; Ramdas, Kamalini; Subburaman, Ganesh-Babu B.; Ravilla, Thulasiraj (Management Science, 2023)
Telemedicine is increasingly used across the developing world to expand access to healthcare, to improve outcomes, and to reduce costs. One common model is that of telemedicine centers, which are small primary care facilities run by midlevel (nonphysician) providers who conduct a preliminary examination and then facilitate a telemedicine visit with a remote physician in real time. However, the impact of this channel of care delivery—particularly on existing physical healthcare-delivery channels—has not been thoroughly examined. We use data from one of the largest tele-ophthalmology implementations in the world to examine this issue. Using a quasi-experimental difference-in-differences approach, we find that opening a nearby telemedicine center generates a 31% increase in the overall network visit rate from the population within 10 km of the new center, 62% of which is driven by new patients, suggesting a substantial increase in access. The rate of eyeglasses prescriptions to correct for simple refractive errors increases by 18.5%, whereas the rate of cataract surgery to replace the natural lens in a patient’s eye with an artificial lens remains unchanged. The increase in access and treatment rates does not significantly impact the direct costs incurred by patients, but reduces their indirect costs (measured as travel distance) by 30% (12 km). Finally, we find significant spatial heterogeneity in these effects, which vary with the distance of patients to facilities. These results have important implications for the design of telemedicine networks and the portfolio of healthcare services provided through them. This paper was accepted by Stefan Scholtes, healthcare management. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4488 .